Profit persistence and stock returns. Issue 37 (8th August 2016) - Gschwandtner, Adelina; Hauser, Michael
ABSTRACT: This article attempts to assemble further empirical evidence on the relationship between the product and the financial market. Drawing back on work in industrial organization, we analyse the relationship between profit persistence and factor-adjusted stock returns looking at about 2000 listed US firms over the last 34 years. While the relationship between (current, lagged and unexpected) profits/earnings and returns has been extensively analysed before, to our knowledge this is the first study to look at the relationship between stock returns and profit persistence . We interpret profit persistence as a result of market competition and innovation of the firm. It is shown that firm-specific long-run profit persistence after correction for other additional economic fundamentals of the firm has a positive impact on four-factor adjusted returns and a negative impact on their volatility.